Analisis Sistem Informasi Laporan Kinerja (LAPKIN) Menggunakan Metode PIECES pada Bagian Perencanaan Sekretariat Daerah Kota Palembang - Arsika Arsika; Gusmelia Testiana (PT Jurnal Cendekia Indonesia, 2026)
The Performance Report Information System (LAPKIN) is an information system used to support the preparation and management of government agency performance reports. This study aims to analyze the quality of the LAPKIN Information System implemented in the Planning Division of the Regional Secretariat of Palembang City using the PIECES framework, which consists of Performance, Information, Economy, Control, Efficiency, and Service aspects. The research employed a descriptive approach with qualitative methods. Data were collected through direct observation, interviews with system users, questionnaires, and documentation during the internship program. The findings indicate that the LAPKIN Information System has generally supported the performance reporting process effectively by facilitating data management, improving report preparation, and reducing administrative processing time. However, several aspects still require improvement, particularly system performance during peak usage, data input efficiency, information security, and user interface design. The PIECES analysis proved effective in identifying the strengths and weaknesses of the system and providing recommendations for future improvements. The results of this study are expected to serve as evaluation material for enhancing the quality of the LAPKIN Information System and supporting more effective, efficient, and accountable performance reporting within the Regional Secretariat of Palembang City.